Hermeneutika Al-Qur’an Untuk Pembebasan : Telaah Kritis Pemikiran Hassan Hanafi - Ilham B. Saenong (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2004)
No hermeneutics per se, absolute, and universal. Hermeneutics always has a particular dimension and has been the integral part of social revolution. The current heading to a more praxis-oriented is much more tangible in Hassan Hanafi’s thought in hermeneutics. It also differentiated Hanafi from others contemporary mufassir (hermeneut) as well. A few Muslim scholars who pay close attention to the notion of liberation in Islamic teaching. Moreover, taking the risk to work laboriously to elaborate the method of interpreting al-Qur’an - which has something to do with the suffering of the oppressed groups. The writing has worked on the background, Hanqfi’s position as an eminence Islamic thinker, and his relation to the others contemporary Islamic thinkers, along with a bit of critical notes.